"Urban Ecology Under Fire": Water Supply in Madrid During the Spanish Civil War (1936–1939). Issue 2 (2nd August 2014) - Gorostiza, Santiago; March, Hug; Sauri, David
Abstract This paper investigates the critical role of workers to enhance the resilience of water supply services in cities at war through analyzing the case of Madrid and the Madrid water company Canales del Lozoya during the Spanish Civil War (1936–1939). We argue that securing the protection of vital urban flows mediated through infrastructures is a key objective of cities under attack. In doing so we contend that examining how those affected by the interruption of these flows cope with the situation represents a valuable but largely neglected form of water management. We illustrate how quotidian knowledge about the urban geography of water flows may have important repercussions for the war effort itself. In a nutshell, the case of Madrid offers an early account of the critical role of water workers in sustaining "urban ecologies under fire" securing the complex urban metabolism while also contributing to the struggle against invading forces.